Current Knowledge on Novel Semi-Arid Photovoltaic Ecosystems, Their Impacts on Biodiversity and Implications for the Sustainability of Renewable Energy Production - Esperanza C. Iranzo; José Manuel Nicolau; Ramón Reiné; Jaume Tormo (Land, 2025)
The transition from fossil fuels to renewable energy is fundamental to the mitigation of global climate change. Renewable power capacity is increasing globally, and solar photovoltaics will be the dominant renewable energy source by 2050. Photovoltaic parks (PVPs) require great expanses of land, usually in drylands, creating impacts that can compromise the sustainability of surrounding ecosystems and PVPs. But both novel ecosystems in PVPs and the effect of PVPs on ecosystems are rarely studied. This paper reviews the current knowledge on the impact of PVPs on arid and semi-arid ecosystems and describes the structure and functioning of these novel ecosystems, including changes in microclimatic conditions, soil properties, vegetation and fauna, and shows how these factors hinder the full recovery of ecosystems in PVPs. Ensuring that we do not sacrifice biodiversity for clean energy production restoration is necessary; hence, we address the limitations and challenges of restoring ecosystems within PVPs and suggest the use of modern ecological restoration techniques and the incorporation of grazing into rational planning. More research is needed to fully understand the long-term impacts and interactions of PVPs with the environment, the evolution of novel ecosystems in PVPs and the restoration techniques needed to achieve the long-term sustainability of these infrastructures.